MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA MELALUI MODEL INKUIRI BERBANTUAN AUDIO VISUAL PADA SISWA KELAS VI SD NEGERI MODEL TERPADU MADANI PALU - Yusuf S., Muh. (JSTT, 2015)
This article was derived from classroom action research report which entitled Improving Activity Science and Learning Outcome Through Inquiry Model supported by Audio Visual ad Class VI of SD Negeri Model Terpadu Madani Palu. The focus of the learning was transfer and transformation of electrical energy. The instruments to collect the data were pre-test, observation sheet for teacher and students activities, and post-test. The result of a research shown that there is any improvement of students activity with 65,47% achievement in cycle I and 82,89% achievement in cycle II. For the learning outcome, the classical mastery learning reach 83,33% in cycle I and reach 91,67% in cycle II. Those achievements are the accumulation of two times meeting in every cycle. Therefore, we can conclude that inquiry learning model with audio visual aided could improve activity and science learning outcome of Class VI students of SD Negeri Model Terpadu Madani Madani Palu.